SISTEM INFORMASI PEMINJAMAN DAN PENGEMBALIAN ALAT-ALAT LABORATORIUM DESAIN KOMUNIKASI VISUAL SMKN 6 KUPANG BERBASIS WEB - Moruk, Fransiskus Xaverius; Sumarlin (Jurnal Publikasi Manajemen Informatika, 2025)
The information system for borrowing and returning laboratory equipment is a solution to increase efficiency and effectiveness in the management of tools in the Visual Communication Design (DKV) laboratory of the State Vocational High School 6 Kupang. The borrowing process that has been carried out manually has the potential to cause various problems, such as delays in returns, loss of tools, and difficulties in collecting inventory data. This research aims to design and build a web-based laboratory equipment lending and return management system that can simplify the process of borrowing and returning equipment, as well as minimize the risk of loss and damage through accurate and real-time recording. The system development method used is the Waterfall method, which includes needs analysis, design, implementation, testing, and maintenance. This research is expected to be a web-based system that can make it easier for students to borrow and return tools online, as well as store all borrowing data in a centralized database. With this system, it is hoped that the management of DKV laboratory equipment at the State Vocational High School 6 Kupang can run more efficiently and transparently.